2023
DOI: 10.1002/anie.202306115
|View full text |Cite
|
Sign up to set email alerts
|

Organopotassium‐Catalyzed Silylation of Benzylic C(sp3)−H Bonds

Baptiste Neil,
Lamine Saadi,
Louis Fensterbank
et al.

Abstract: Benzylsilanes have found increasing applications in organic synthesis as bench-stable synthetic intermediates, yet are mostly produced by stoichiometric procedures. Catalytic alternatives based on the atomeconomical silylation of benzylic C(sp 3 )À H bonds remain scarcely available as specialized directing groups and catalytic systems are needed to outcompete the kinetically-favored silylation of C(sp 2 )À H bonds. Herein, we describe the first general and catalytic-in-metal undirected silylation of benzylic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…27 Finally, we investigated the mechanism of the reaction. In accordance with our previous study, 17 we postulated that facile metalation of allylic C(sp 3 )−H bonds should readily take place upon anionic decomposition of the silylated diazene. To this end, we first demonstrated that allyl potassium intermediates are generated during the silylation of two representative substrates, namely, allylbenzene 3 and allylamine 25.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…27 Finally, we investigated the mechanism of the reaction. In accordance with our previous study, 17 we postulated that facile metalation of allylic C(sp 3 )−H bonds should readily take place upon anionic decomposition of the silylated diazene. To this end, we first demonstrated that allyl potassium intermediates are generated during the silylation of two representative substrates, namely, allylbenzene 3 and allylamine 25.…”
supporting
confidence: 91%
“…In line with these observations and our previous computational results on the silylation of benzylic C(sp 3 )−H bonds, 17 we propose the general catalytic cycle presented in Scheme 6C, which begins with an initiation step between tBuOK and 1a (not shown) that affords the π-allyl potassium species A. The latter then rapidly undergoes K/Si transmetalation with diazene 1a to give the potassium diazenyl complex B bound to the linear allylsilane moiety via a cation−π interaction.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Recently rediscovered and synthetically versatile N -aryl- N′ -silyldiazenes begin to find useful applications as latent aryl pronucleophiles. Anionic Lewis bases mediate their desilylation, generating aryl-substituted diazenyl anions that eventually collapse into dinitrogen and aryl nucleophiles that can be decorated with a broad spectrum of functional groups. Accordingly, we have been seeking new reactions for these silicon-masked aryl pronucleophiles.…”
mentioning
confidence: 99%